Phenomenological Subjects. Apostolescu, I. (Ed.). (2020). The Subject(s) of Phenomenology: Rereading Husserl. Cham: Springer Nature. - Kebuladze, Vakhtang (Sententiae, 2021)
Review of Apostolescu, I. (Ed.). (2020). The Subject(s) of Phenomenology: Rereading Husserl. Cham: Springer Nature.